Fabrication and Characterization of a W-Band Cylindrical Dielectric Resonator Antenna-Coupled Niobium Microbolometer - M. Abdel-Rahman; M. Kamran Saleem; Najeeb Al-Khalli; Nacer Debbar; Majeed A. S. Alkanhal; Abdelrazik Sebak (International Journal of Antennas and Propagation)
We report on the fabrication and characterization of a novel antenna-coupled detector configuration for detection at 94 GHz, a coplanar waveguide- (CPW-) fed, slot-excited twin dielectric resonator antenna- (DRA-) coupled niobium (Nb) microbolometer. The antenna is based on two low permittivity cylindrical dielectric resonators (CDRs) excited by rectangular slots placed below the CDRs. The antenna resonant currents are fed to an Nb microbolometer by the means of a CPW feed. The ceramic DRA structure is manufactured using a novel fabrication process that enables patterning an SU-8–Alumina (Al2O3) nanopowder composite using conventional photolithography. The detector measured a voltage responsivity of 0.181 V/W at a modulation frequency of 150 Hz. The detector measured a time constant of 1.94 μs. The antenna radiation pattern of the developed detector configuration was measured and shows a good agreement with the simulation.